Mycobacterium ulcerans not detected by PCR on human skin in Buruli ulcer endemic areas of south eastern Australia. - Anita Velink; Jessica L Porter; Timothy P Stinear; Paul D R Johnson (Public Library of Science (PLoS), 2023)
Introduction Mycobacterium ulcerans (MU) causes Buruli ulcer (Buruli), a geographically restricted infection that can result in skin loss, contracture and permanent scarring. Lesion-location maps compiled from more than 640 cases in south eastern Australia suggest biting insects are likely involved in transmission, but it is unclear whether MU is brought by insects to humans or if MU is already on the skin and inoculation is an opportunistic event that need not be insect dependent. Methods We validated a PCR swab detection assay and defined its dynamic range using laboratory cultured M. ulcerans and fresh pigskin. We invited volunteers in Buruli-endemic and non-endemic areas to sample their skin surfaces with self-collected skin swabs tested by IS2404 quantitative PCR. Results Pigskin validation experiments established a limit-of-detection of 0.06 CFU/cm2 at a qPCR cycle threshold (Ct) of 35. Fifty-seven volunteers returned their self-collected kits of 4 swabs (bilateral ankles, calves, wrists, forearms), 10 from control areas and 47 from endemic areas. Collection was timed to coincide with the known peak-transmission period of Buruli. All swabs from human volunteers tested negative (Ct ≥35). Conclusions M. ulcerans was not detected on the skin of humans from highly Buruli endemic areas.